Ethnic group parents’ beliefs toward English medium instruction in school: A case of Kailali district (Siddhajyoti Interdisciplinary Journal, 2020)
This research paper tries to explore the beliefs of ethnic group parents whose children study in private and community based schools in Kailali having English medium instruction (EMI). It has linked the education system in terms of English medium instruction. This study has built the framework of study on the basis of interview taken deeply from the ethnic group parents. The documented and recorded data show that English medium instruction is not on behalf of their mother tongue, learning style, environment and pace of learning. The only English medium instruction is applied currently in most of the private and government schools in Nepal. The beliefs of ethnic group parents illustrate that their children are not benefitted from English medium instruction regarding learning, doing homework and being interested in reading activities. Their views reveal the idea that use of only English medium instruction is being affected from the thinking of dominating their children’s languages. Finally, the beliefs of ethnic group parents show that the use of their languages (i.e. Tharu, Tamang, and Magar) in the schooling can attract children to the schools, doing homework, and decreasing the dropout rate of children from the school education.